One‐year swallowing outcomes following transoral laser microsurgery +/− adjuvant therapy versus primary chemoradiotherapy for advanced stage oropharyngeal squamous cell carcinoma. (7th February 2016) - O'Hara, J.; Goff, D.; Cocks, H.; Moor, J.; Hartley, C.; Muirhead, C.; Patterson, J.
Abstract : Objectives: To assess the between‐group change in swallowing function from baseline to 12 months following treatment, for patients treated for resectable stage III and IVA oropharyngeal squamous cell carcinoma. To assess the within‐group change in swallowing function between 3 and 12 months following treatment. Design: Non‐randomised cohort study. Setting: A single head and neck cancer unit with oncology services held at the nearby regional treatment centre. Participants: Twenty‐five patients treated with Transoral Laser Microsurgery +/‐ adjuvant (chemo)radiotherapy (Transoral Laser Microsurgery) observed alongside an historic cohort of 33 patients treated with (chemo)radiotherapy. Main Outcome Measures: The patient reported MD Anderson Dysphagia Inventory (MDADI), an objective timed Water Swallow Test, and the clinician rated normalcy of diet subsection of the Performance of Swallowing Scale . Results: Between baseline and 12 months, patients treated with primary (chemo)radiotherapy demonstrated greater deterioration in swallowing function compared to Transoral Laser Microsurgery for all 3 swallowing measures. Between 3 and 12 months, the only significant change was an improvement in Performance of Swallowing Scale scores in the (chemo)radiotherapy group. Conclusions: This is the first study to report the results of a complimentary set of swallowing measures for patients treated with Transoral Laser Microsurgery, observed alongside a cohort of (chemo)radiotherapy patients. The preliminary results suggest a benefit in swallowing function for Transoral Laser Microsurgery over (chemo)radiotherapy during the year following treatment.